Integrasi Studi In Vitro dan In Silico dalam Evaluasi Potensi Antibakteri Ekstrak Etanol Jahe Merah (Zingiber officinale var. rubrum) terhadap Escherichia coli dan Staphylococcus aureus - Jackie Petrus Ambaruka; Iqbal Yusuf; Irfan Dwi Sasono (Lembaga Publikasi Ilmiah Nusantara, 2026)
Red ginger (Zingiber officinale var. rubrum) is a medicinal plant rich in phenolic compounds and has considerable potential as a natural antibacterial agent to address the growing challenge of antimicrobial resistance. This study aimed to evaluate the antibacterial activity of red ginger ethanolic extract against Escherichia coli and Staphylococcus aureus using an integrated in vitro and in silico approach. The extract was prepared by maceration with 96% ethanol and evaluated using the disk diffusion method at concentrations of 25%, 50%, 75%, and 100%. The data were analyzed using one-way analysis of variance (ANOVA), followed by Tukey's honestly significant difference (HSD) test at a significance level of α = 0.05. The in silico analysis was performed through molecular docking against the DNA gyrase enzyme using four major bioactive compounds of red ginger, namely 6-gingerol, 8-gingerol, 10-gingerol, and 6-shogaol. The results demonstrated that increasing extract concentration significantly enhanced antibacterial activity (p < 0.001). The highest inhibition zones were observed at the 100% extract concentration, reaching 16.57 ± 0.42 mm against E. coli and 19.13 ± 0.35 mm against S. aureus, although chloramphenicol, used as the positive control, produced larger inhibition zones. Staphylococcus aureus exhibited greater susceptibility to the extract than E. coli. Molecular docking analysis revealed that all tested bioactive compounds showed favorable binding affinities toward DNA gyrase, with 10-gingerol exhibiting the lowest binding affinity (−8.0 kcal/mol), indicating the most stable ligand–protein interaction. The integration of in vitro and in silico findings suggests that the antibacterial activity of red ginger ethanolic extract may involve disruption of bacterial cell membrane integrity as well as potential inhibition of DNA gyrase. These findings support the potential application of red ginger as a promising natural antibacterial agent and provide a scientific basis for further investigations involving minimum inhibitory concentration (MIC), minimum bactericidal concentration (MBC), toxicity assessment, and instrumental characterization of its bioactive compounds.